PENGARUH PENERAPAN STANDAR OPERASIONAL PROSEDUR TERHADAP KUALITAS PELAYANAN DI PELABUHAN PERIKANAN NUSANTARA SIBOLGA PROVINSI SUMATERA UTARA - Tanjung, Yenni O.; Zain, Jonny; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrakThe success of a wild fishery business is strongly influenced by the quality of service, one of which is by applying the operational standard of procedure as guidance on the performance of employees in carrying out the activities of the wild fishery business in the fishing port. SOP as a running of port activities, it is necessary to do research on the effect of SOP on the quality of service at the fishery port. This study aims to determine the effect of standard operating procedures on the quality of service. This research was conducted at Sibolga Fishing Port. This research use purposive sampling method that is spreading of questionnaire for employee of Sibolga Fishing Port which has served as Civil Affair Employee. The sample used in this study was 42 respondents, where data were collected through questionnaires distributed. Analysis based on the respondent's answers obtained through questionnaires distributed by researchers. Mechanical analysis using multiple linear regression analysis with SPSS 20. These results indicate that Standard Operating Procedure 0.984 application has no significant value which means the Standard Operating Procedure significantly does not affect the level of service quality as well as internal control activities have 0.796 significant value and the competence of human resources has 0.743 significant value means has no significant effect on service quality.Key word : Standard Operating Procedure, Fishing port, Internal control system, Human resources competence, Service quality, Fisherman satisfaction.